ISOLASI DAN IDENTIFIKASI SENYAWA FLAVON DARI EKSTRAK ETIL ASETAT BRUCEA JAVANICA Merrill - Megawati Megawati; A Darmawan; M Angelina; S Fajriah; M Hanafi; P D Lotulung (Jurnal Kimia Terapan Indonesia, 2011)
Buah Makasar (Brucea javanica Merrill)is a wild ornamental plant and one of the traditional medicine plants. Isolation andpurification of ethyl acetate extract of B.javanica using silica gel column chromatography with ethyl acetatem-hexane as a mobile phase gradually obtained a pure compound as yellow crystals. It was identified by using infrared spectrophotometer (IR), LC-MS (liquid chromatography mass spectrometer) and ID- and 2D-NMR (nuclear magnetic resonance), compound a identified as 6-hydroxy-2-(3,4,5-trihydroxyphenyl}-4H-chromen-4-one, a flavones compound with molecular formula Cl5HI006 and molecular weight of 287.18 m/z.Keywords: Brucea javanica Merrill, buah makasar, flavones,6-hydroxy-2-(3,4,5-trihydroxyphenyl)-4H-chromen-4-one